Students’ Perception of Using Humor in Teaching English at XI Grade in SMAN 2 Tilatang Kamang - Yana, Rahma; Syahrul, Syahrul (International Journal of Humanities, Education, and Social Sciences, 2023)
The goals of this research were to find out the students’ perception of using humor in teaching English class and to find out the difference between male and female students’ perceptions of using humor in teaching English at XI grade in SMAN 2 Tilatang Kamang. The researcher found several problems related to the use of humor in teaching English. First, some students were noisy in the classroom and did not focus on learning. Second, some students gave positive and negative responses to teachers who used humor in the classroom. Third, there were differences in responses between male and female students regarding the use of humor in the classroom. Last, some students didn't like humor in class. The researcher used a descriptive quantitative method. The researcher chose XI grade. In this study, the researcher used total sampling because the population was less than 100. The researcher used a closed questionnaire. Based on this research, it can be concluded that used humor in teaching had a positive category as marked by the average score of the 4 categories of humor in learning English such as caricature humor was 78.07%, short story or anecdotes humor was 78.58%, special humor was 74.13%. Unplanned was 74.13%. Then, female students more preferable to caricature humor which was 78.72%, and male students more preferable to a short story which was 78.39%. Next, female students had better perceptions than male students which was female was 75,73% while male were 73,81%.